PENERAPAN MODEL PEMBELAJARAN BERBASIS STEM DALAM UPAYA MENINGKATKAN HASIL BELAJAR KIMIA SISWA KELAS XI MIPA 4 SMA NEGERI 7 DENPASAR TAHUN PELAJARAN 2019/2020 (LP3M Universitas PGRI Mahadewa Indonesia, 2021)
The purpose of this study was to determine whether the application of STEM-based learning models can improve learning outcomes and how students respond to dynamic equilibrium material. This research is a classroom action research designed through action research in classroom learning activities. This research was conducted at SMA Negeri 7 Denpasar in October 2019 in the odd semester. The subjects of this study were students of class XI MIPA 4 SMA Negeri 7 Denpasar, and the object of this study was the application of STEM-based learning models and student responses to chemistry learning outcomes. In this study, four stages of the activity process were used which included (1) planning, (2) action, (3) observation, and (4) evaluation and reflection. Data collection techniques using test and observation methods. Data collection in cycle I and cycle II was carried out by using the technique of assessing student test results as numerical data, while data collection used observational techniques for qualitative data. The research results obtained from the average value of the comparison of pre-cycle, cycle I, and cycle II there is an increase. So the application of STEM-based learning models can improve student learning outcomes, and there is student response in the application of STEM-based learning models to improve student learning outcomes on equilibrium material in class XI MIPA 4 SMA Negeri 7 Denpasar for the 2019/2020 academic year.